Find: $$\lim_{n\rightarrow\infty}\frac{\sin\left(x+\frac{1}{n}\right)-\sin\left(x\right)}{\sin\left(x+\frac{1}{n}\right)}$$ as $x\in\mathbb{R}$ My progress:


$$\lim_{n\longrightarrow\infty} \ \ {1}-\frac{\sin\left(x\right)}{\sin\left(x+\frac{1}{n}\right)}=1-\lim_{n\longrightarrow\infty}\frac{\sin\left(x\right)}{\sin\left(x+\frac{1}{n}\right)}$$ at this point I got stuck.

I can't evaluate the Taylor series of $\sin(x+\frac{1}{n})$ because $n$ is not fixed

(even if we'll suppose that there exist some $\epsilon>0$ and there exists $ N\in\mathbb{N}:\forall n\geq N$ s.t: $$-\epsilon<\frac{1}{n}<\epsilon$$ it doesn't seem like a formal argument to me)

(I might be very wrong - it's only my intuition).

Also trying to apply L'Hopital's rule for this expression isn't much helpful.

  • 1
    $\begingroup$ Have you tried using continuity of the $\sin$ function? If you have not proven that for continuous functions: $$\lim_{ x\to a} f(x) = f\left( \lim_{x \to a} x \right)$$ then how about using the sum of angles formula for $\sin$ and see if that simplifies anything. $\endgroup$ – InterstellarProbe Jul 5 '18 at 13:36

If $\sin(x) = 0$ then $$ \frac{\sin\left(x+\frac{1}{n}\right)-\sin\left(x\right)}{\sin\left(x+\frac{1}{n}\right)} = 1 \to 1 $$ for $n \to \infty$, otherwise $\sin\left(x+\frac{1}{n}\right) \to \sin(x) \ne 0$ and therefore $$ \frac{\sin\left(x+\frac{1}{n}\right)-\sin\left(x\right)}{\sin\left(x+\frac{1}{n}\right)} \to \frac{\sin(x) - \sin(x)}{\sin(x)} = 0 \, . $$

So there is no need to use L'Hospital's rule in the case $\sin(x) = 0$, but doing so would give the same result: $$ \lim_{n \to \infty}\frac{\sin\left(x+\frac{1}{n}\right)-\sin\left(x\right)}{\sin\left(x+\frac{1}{n}\right)} = \lim_{h \to 0}\frac{\sin\left(x+h\right)-\sin\left(x\right)}{\sin\left(x+h\right)} \stackrel{\text{(H)}}{=} \lim_{h \to 0} \frac{\cos(x+h)}{\cos(x+h)} = 1 \, . $$


From here

$$\lim_{n\longrightarrow\infty} \ \ {1}-\frac{\sin\left(x\right)}{\sin\left(x+\frac{1}{n}\right)}=1-\lim_{n\longrightarrow\infty}\frac{\sin\left(x\right)}{\sin\left(x+\frac{1}{n}\right)}$$

we have that for $\sin x\neq 0$

$$\lim_{n\longrightarrow\infty}\frac{\sin\left(x\right)}{\sin\left(x+\frac{1}{n}\right)}=\frac{\sin x}{\sin x}=1$$

and for $\sin x =0$


  • $\begingroup$ I disagree for $x=0$. try to apply L'Hopital's... $\endgroup$ – Jneven Jul 5 '18 at 13:54
  • $\begingroup$ for x=0 we obtain directly the result, we don’t need l’Hopital $\endgroup$ – user Jul 5 '18 at 14:03
  • $\begingroup$ @gimusi Hey, I have a question that is more or less relevant to this question. Do you know why the substitution $h=\frac{1}{n}$ and using the derivative definition fails to give a good answer in this problem? $\endgroup$ – Sorfosh Jul 5 '18 at 20:17
  • $\begingroup$ @Sorfosh If we consider $$\lim_{h\to 0}\frac{\sin\left(a+h\right)-\sin\left(a\right)}{\sin\left(a+h\right)}$$ for $\sin a \neq 0$ it is equal to $0$ and for $\sin a = 0$ it is equal to $1$. In both case there are not the conditions to apply l'Hopital. $\endgroup$ – user Jul 5 '18 at 20:21
  • $\begingroup$ @gimusi I mean $\lim_{n\rightarrow\infty}\frac{\sin\left(x+\frac{1}{n}\right)-\sin\left(x\right)}{\sin\left(x+\frac{1}{n}\right)}=lim_{h\rightarrow0^{+}}\frac{\sin\left(x+h\right)-\sin\left(x\right)}{\sin\left(x+h\right)}=lim_{h\rightarrow0^{+}}\frac{h(sin\left(x+h\right)-\sin\left(x\right))}{h\sin\left(x+h\right)}$ Now split it up and use the derivative definition. $\endgroup$ – Sorfosh Jul 5 '18 at 20:25

Say $x\ne \pi\cdot k$ where $k\in \mathbb{Z}$

$$ \lim_{n\rightarrow\infty}\frac{\sin\left(x+\frac{1}{n}\right)-\sin\left(x\right)}{\sin\left(x+\frac{1}{n}\right)}=\lim_{n\rightarrow\infty}\frac{\sin\left(x+\frac{1}{n}\right)-\sin\left(x\right)}{\frac{1}{n}}\cdot \lim_{n\rightarrow\infty}{{1\over n}\over{\sin\left(x+\frac{1}{n}\right)} } = \cos x\cdot 0$$

And if $x= \pi\cdot k$ then the limit is $1$.


use $\sin(A + B) = \sin(A)\cos(B) + \cos(A)\sin(B)$

$$\frac{\sin\left(x+\frac{1}{n}\right)-\sin\left(x\right)}{\sin\left(x+\frac{1}{n}\right)}$$ = $$\frac{\sin(x)\cos(\frac{1}{n}) + \cos(x)\sin(\frac{1}{n}) - \sin(x)}{\sin(x)\cos(\frac{1}{n}) + \cos(x)\sin(\frac{1}{n})}$$

for sin(x) not zero $$\lim_{n\rightarrow\infty}\frac{\sin\left(x+\frac{1}{n}\right)-\sin\left(x\right)}{\sin\left(x+\frac{1}{n}\right)}$$

$$=\lim_{n\rightarrow\infty}\frac{\sin(x)\cos(\frac{1}{n}) + \cos(x)\sin(\frac{1}{n}) - \sin(x)}{\sin(x)\cos(\frac{1}{n}) + \cos(x)\sin(\frac{1}{n})}$$

$$=\frac{\sin(x)\cos(0) + \cos(x)\sin(0) - \sin(x)}{\sin(x)\cos(0) + \cos(x)\sin(0)}$$

$$=\frac{\sin(x).1 + \cos(x).0 - \sin(x)}{\sin(x).1 + \cos(x).0}$$

$$=\frac{\sin(x) - \sin(x)}{\sin(x)}$$

$$ = 0$$

for sin(x) = 0, you can again plug in values and simplify to

$$\frac{\sin(\frac{1}{x})}{\sin(\frac{1}{x})} = 1$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.